A STUDY ON THE ABILITY OF THE EIGHTH YEAR STUDENTS OF SMP NEGERI 4 PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Feni Harti; Fadly Azhar; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive research aimed to find out the ability of the eighth year students of SMP Negeri 4 Pekanbaru in comprehending recount texts. The population of the research was the eighth year students of the school. The number of the population were 332 students. Thirty five of them were the samples selected by using cluster random sampling technique. The instrument to collect the data was a reading test. The total number of test items was thirty questions. The test consisted of 5 short recount texts. Each text consists of 6 questions which cover the components of reading and the components of recount text namely finding main ideas, finding factual information, finding the meaning of difficult words, finding references, finding restatements and finding social functions. The data were analyzed by classifying them into five levels of ability: very poor, poor, mediocre, good, and excellent. Based on the result showed that the students’ reading ability of the eighth year students of the school in comprehending recount texts was in good level with the mean score was 74.28. The implication of this research is that the eighth year students of the school have a good ability in reading recount texts.Key Words: Students’ Ability, Reading, Recount Texts.